A música sertaneja é a que eu mais gosto! : Um estudo sobre a construção do gosto a partir das relações entre jovens estudantes de Itumbiara-GO e o Sertanejo Universitário - Santos, Daniela Oliveira dos (2012)
This research\'s main objective is to understand how the taste is built from the relationships between youth students and the Sertanejo Universitário. Seven 14 17 years old teenager students were chosen from Colégio da Polícia Militar - Unidade Dionária Rocha, located in the city of Itumbiara-GO, to participate of the investigation. More specifically, aimed to identify practices these young with the Sertanejo Universitário, and to focus how the taste is appropriated through various practices and, therefore, understand the learning process within those reationships. In order to better understand the field in which this research is part, the literature review presented studies associated with youth in contemporary, the relationship between young-music-school and young-music-taste, plus a brief history of ―música sertaneja‖ especially its current side, the Sertanejo Universitário. The second chapter provides an overview of the Sociology of Music, with emphasis on sociologists who contributed to the growth of the area. In the same chapter, the taste theory of Antoine Hennion is shown, and its foundations based on three pillars: the taste as a performance, the construction of taste with support in the collective activity and reflexivity of the amateur. The third chapter details the methodological procedures applied to research, choosing the narrative interviews as a technique for data collection. Also in this chapter, there the observations made in school and during an event of the ―música sertaneja‖, there is from a concert held on the Arraiá in Itumbiara-GO. For the analysis, I use the technique of triangulation of data, exposing the youth narrated about their practices and performances with the Sertanejo Universitário, in what respects their tastes were supported by a collective activity and how it happened moments of reflexivity. The observations allowed the visualization of the actions of youth involved with the music, and equally important reflections on the school as a space where youth perform various musical practices. In addition, I state my studies about the taste is presented as a result of a series of practices that provides youth with music, such as the constant listening, singing, dancing, among others. This research also provides to know the strategies used by youth students surveyed for their musical practices. Thus, the taste is built in diverses practices that were perceived the youth executed an instrument (performance), in the many who exhibited the importance with your colleagues, friends and family (collective activity) and when through a word or even the absence, gave evidence of his taste through a reflective activity.